Exploring the causality between economic growth, financial development and inflation in sixteen high-income countries (Revista de Estudos Sociais, 2021)
This paper examined the relationship between economic growth, inflation, stock market development, and banking sector development for a panel of sixteen high-income countries for the period from 2001 to 2016, by using the mechanism impulse response functions and Granger causality tests derived from a panel vector autoregressive model. The evidence of bidirectional causality between all variables in the model was found. Overall, feedback and supply-leading theories have been confirmed in the literature. A plus sign in the relationship between the development of the banking sector and the stock market with economic growth was found. Therefore, stock market development and banking sector development stimulate the economy.